(untitled) (Research, Society and Development, 2021)
The cotton growing area is one of the most expanding, presenting itself as an important economic alternative, with Brazil being the fifth largest producer in the world. The objective was to evaluate the endoparasitic profile that affect quails from two farms in the city of Porto Velho - RO. The research was carried out in two laying quail farms in the city, from August to November 2019. Twenty-five samples were collected from each farm, totaling 50 samples, processed by the WILLIS-MOLLAY method for qualitative identification of endoparasites. All 25 samples (100%) from G1 were positive, making it possible to identify parasites of the genera Echinuria spp., Trichostrongylus spp., Amidostomum spp., Heterakis gallinarum, Choanotaenia infundibulum, and oocysts of Eimeria spp. In the second farm, 15 samples (60%) had endoparasites, including Ascaris spp, Giardia spp., Trichostrongylus spp., with a higher prevalence of Amidostomum spp. The exposition of this parasitic fauna in quails demonstrates the importance of research in the cotton industry and its potential development.